Storability as affected by seed pelleting and priming in fennel (Foeniculum vulgare) - SINGH, SURYAPAL; SINGH, HARSHITA; MOR, V S (The Indian Journal of Agricultural Sciences, 2021)
The present study was carried out at Laboratory of Department of Seed Science and Technology, CCS Haryana Agricultural University, Hisar to ascertain the effect of pelleting and priming material on storability of fennel (Foeniculum vulgare Mill.) seeds during 2017-19. The treatments comprising of 7 pelleting treatments, 14 priming treatments and a control were laid out in Completely Randomized Design with three replications. The seed quality relating to physiological traits decreased with advancement in storability except for electrical conductivity. Better retention of seed quality characters, viz. standard germination, speed of emergence, seedling dry weight, vigour indices was observed in the seeds pelleted with Captan (3 g/kg) + Imidacloprid (2 g/kg) followed by KNO3 (1%) and neem leaf powder (100 g/kg seeds) after 18 months of storage (except seedling length and seed vigour index-I). The minimum EC was recorded in seeds primed with Trichoderma viride (8 g/kg seed), followed by KNO3 (1%) and seeds pelleted with Captan @3 g/kg + Imidacloprid @2 g/kg. Therefore, it can be concluded that in order to maintain better seed quality of fennel during storage, seed pelleting proved superior over seed priming that ought to be given as pre-sowing treatment not as pre-storage treatment.